Extension worker competencies needed for effective management of self-help groups (SHG) in Gombe state - Gombe, Sani Yakubu; Suandi, Turiman; Ismail, Ismi Arif; Omar, Zoharah (Universiti Putra Malaysia Press, 2015)
Inadequate number of competent extension workers in Nigeria has made the work very tedious and resulted to poor performance in the field. The regulatory agencies were found to be training and retraining the personnel on various areas of the extension service, but still, extension workers were found lacking the skills required for self-help groups’ (SHGs) formation, management and evaluation, which resulted to non-availability of the groups in some communities or low performance where they are found. This paper discusses competencies of the extension worker in terms of knowledge, skills, attitude and personal characteristics that can be acquired or developed, with specific focus on identifying the competencies required by both baseline extension workers and their supervisors on initiating, forming, managing and evaluating SHGs. Delphi method was used in the study and the result revealed that 28 competencies are required to effectively build solid and formidable SHGs. These competencies were categorized into four main groups namely; organizational tradition and guidance, leadership building, system or style, social and external personal skills, and resource management skills, for easy training and assimilation of the extension workers. The paper recommends carrying out training of extension workers systematically; especially in group activities since the SHGs is their main tool of work. Also, to enhance the competency of the extension workers, professional values and training opportunities directly related to the needs of the extension worker should be stressed.